A Meta-Analysis of Randomized Controlled Trials Concerning the Efficacy of Transversus Abdominis Plane Block for Pain Control After Laparoscopic Cholecystectomy - Wang, Weihua; Wang, Lishan; Gao, Yan (Frontiers in Surgery, 2021)
Background and Purpose: Transverse abdominis plane (TAP) block has been suggested to reduce post-operative pain after laparoscopic cholecystectomy (LC). However, the literature is divided on whether ultrasound (USG)-guided TAP block is effective for pain control after LC. The present meta-analysis therefore evaluated the efficacy of USG-guided TAP block vs. controls and port site infiltration for pain control after LC. Methods: A comprehensive literature search of online academic databases was performed for published randomized controlled trials (RCTs) for studies published to January 31, 2021. The primary outcome analyzed was post-operative pain score at 0, 6, 12, and 24 hours post-surgery, both during rest and while coughing. Secondary outcomes included morphine consumption and post-operative nausea and vomiting (PONV) incidence. Results: A total of 23 studies with data on 1,450 LC patients were included in our meta-analysis. A reduction in pain intensity at certain post-operative timepoints was observed for USG-guided TAP block patients compared to control group patients. No reduction in pain intensity was observed for patients receiving USG-guided TAP block patients vs. conventional Port site infiltration. Conclusion: This meta-analysis concludes that TAP block is more effective than a conventional pain control, but not significatively different from another local incisional pain control that is port site infiltration. Additional prospective randomized controlled trials are required to further validate our findings.